2005
DOI: 10.1038/nature03550
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibration of hydrostatic pressure in blebbing cells

Abstract: Letter to NatureCurrent models for protrusive motility in animal cells focus on cytoskeleton-based mechanisms, where localized protrusion is driven by local regulation of actin biochemistry 1-3 . In plants and fungi, protrusion is driven primarily by hydrostatic pressure 4-6 . For hydrostatic pressure to drive localized protrusion in animal cells 7,8 , it would have to be locally regulated, but current models treating cytoplasm as an incompressible viscoelastic continuum 9 or viscous liquid 10 require that hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
602
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 570 publications
(654 citation statements)
references
References 27 publications
47
602
3
2
Order By: Relevance
“…A simple but direct indication of how stresses and pressures may be out-of-equilibrium in cells over distances smaller than a cell length can be seen in an experiment where liquid was deliberately forced through cells into which passivated quantum dots had been microinjected using an external osmotic gradient (figure 4, GC, TM and LM, manuscript in preparation) using the local perfusion apparatus described in [29]). We found that two parts of the cytoplasm, separated by as little as ~5μm, could be strongly out of hydrodynamic equilibrium.…”
Section: A Minimal Microstructural Model For Cytoplasm: Poroelasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…A simple but direct indication of how stresses and pressures may be out-of-equilibrium in cells over distances smaller than a cell length can be seen in an experiment where liquid was deliberately forced through cells into which passivated quantum dots had been microinjected using an external osmotic gradient (figure 4, GC, TM and LM, manuscript in preparation) using the local perfusion apparatus described in [29]). We found that two parts of the cytoplasm, separated by as little as ~5μm, could be strongly out of hydrodynamic equilibrium.…”
Section: A Minimal Microstructural Model For Cytoplasm: Poroelasticitymentioning
confidence: 99%
“…Blebs in most cells appear directionally uncontrolled, though blebbing of the leading edge thought to power directed motility in certain embryonic [37,38], amoeboid [39], and metastatic tumour cells [40][41][42][43]. Blebs, that protrude at rates of ~0.4 μm.s −1 [29], are more dramatic than standard, controlled protrusive events at the leading edge of motile cells. For example, lamellipodia protrude at ~0.15 μm.s −1 in rapidly moving fish keratocytes [44], and slower in most other cell types.…”
Section: Exhibit 1: Blebbing As a Window Into Cell Hydraulicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models use average values of mechanical constants which arise from complex cellular architecture. Experimentally applied forces and readouts of deformation suggest that cell responses to stress can be modeled using linear elasticity, 8 tensegrity, 53 poroelasticity, 10 viscoelasticity, 30 power-law rheology, 32 and scale-free glassy rheology 3 depending on the magnitude and mode of force application. Finite element analysis remains the most effective tool to apply these constitutive frameworks to complex loading protocols and geometries; a process which is necessary in order to assess cellular responses to forces on multiple spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…An appealing mechanism is hydraulic fracturing caused by a transient contraction of the actomyosin cytoskeleton [4]. This mechanism is based on the idea that the cell interior is poroelastic; a local contraction of the cytoskeleton causes a local pressure buildup that slowly relaxes through water flow in the cytoskeletal network (Fig.…”
Section: Hydraulic Fracturing In Cells and Tissuesmentioning
confidence: 99%